Mestizo Farmers' Knowledge of Entomofauna Is Reflected in Their Management Practices: A Case Study in the Andean-Amazon Foothills of Peru - Beltrán-Tolosa, Lucila Marcela; Cruz-Garcia, Gisella S.; Solis, Reynaldo; Quintero, Marcela (Frontiers in Sustainable Food Systems, 2020)
Local knowledge of entomofauna can influence environmental actions, particularly crop management practices, which can be sustainable or unsustainable. A farmer's decision-making is associated with their knowledge of beneficial insects and pests. This study aimed to assess local knowledge of entomofauna in relation to associated management practices, within a context of socio-cultural and environmental change. The research was carried out in Santa Lucía, a small mestizo village located in the deforestation frontier of the Peruvian Amazon. Mestizos are migrants, or descendants of migrants, from non-Amazonian regions of Peru. First, freelistings were conducted with a group of 19 female and 25 male farmers to evaluate their theoretical knowledge of insects, and to select the most salient insects associated with cassava, maize, and plantain. Second, two focus groups (which separated women and men) evaluated the practical knowledge of management practices for the most salient insects in the context of climate change. The most salient insects were collected and identified to the minimum possible taxonomic level. The results showed that farmers have a negative perception of entomofauna associated with cassava, maize, and plantain, as they considered insects to be harmful to their staple crops. Most farmers are not aware of the importance of beneficial insects such as pollinators and natural enemies. The findings of the study further showed that mestizo farmers did not have any management practices to preserve beneficial entomofauna, half of the insects they regarded as pests did not present any associated management practices, and the other half applied both sustainable (preventive and curative) and unsustainable practices (e.g., use of pesticides). The paper further discusses the dynamics of mestizo local knowledge on entomofauna in a changing environment and concludes that local capacities should be built to enrich knowledge about the recognition, biology, and ecological role of entomofauna (e.g., pollination, natural predation), and associated management practices (e.g., agroecological preventive practices that decrease pest incidence and protect pollinators, instead of curative practices) as an adaptation strategy to climate change.